2013
DOI: 10.1016/j.poly.2012.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Conformational isomerism of trans-[Pt(NH2C6H11)2I2] and the classical Wernerian chemistry of [Pt(NH2C6H11)4]X2 (X=Cl, Br, I)

Abstract: X-ray crystallographic analysis of the compound trans-[Pt(NH2C6H11)2I2] revealed the presence of two distinct conformers within one crystal lattice. This compound was studied by variable temperature NMR spectroscopy to investigate the dynamic interconversion between these isomers. The results of this investigation were interpreted using physical (CPK) and computational (molecular mechanics and density functional theory) models. The conversion of the salts [Pt(NH2C6H11)4]X2 into trans-[Pt(NH2C6H11)2X2] (X = Cl,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…An MM geometry optimization was carried out for each conformer using Gaussian03 . The universal force field was employed using technical details described previously …”
Section: Methodsmentioning
confidence: 99%
“…An MM geometry optimization was carried out for each conformer using Gaussian03 . The universal force field was employed using technical details described previously …”
Section: Methodsmentioning
confidence: 99%
“…DNA polymerase η, a translesion synthase capable of bypassing 1,2-intrastand cross-links formed by cisplatin, is able to insert the correct nucleotide opposite the phenanthriplatin-bound guanine, but cannot proceed further . A detailed mechanism of DNA polymerase η inhibition was inferred from X-ray crystallographic data, which suggested that, despite the rotational freedom typically observed about Pt–amine bonds, the phenanthridine ring imposes a thermodynamic diastereoselectivity on the adduct that plays a significant role in blocking polymerase progression. , Studies with Escherichia coli resembling those conducted by Rosenberg further revealed that phenanthriplatin induces filamentous cell growth in a manner similar to that of cisplatin . Monofunctional platinum­(II) complexes with little biological activity in cultured mammalian cancer cells were not able to replicate this result.…”
Section: Platinum(ii) Compounds With a Mechanism Of Action Different ...mentioning
confidence: 99%
“…Trans complexes can also be prepared directly from [PtL 4 ]­X 2 compounds without the use of hydrochloric acid. Upon heating [PtL 4 ]­X 2 as a suspension in an organic solvent or as a solid under vacuum, the outer-sphere halides substitute the inner-sphere amine or N -heterocycle, exclusively generating the trans isomer. In an attempt to make trans -[PtL 2 Cl 2 ], where L is imidazole, [PtL 4 ]­Cl 2 was treated with HCl. Instead of obtaining the expected product, trans -[PtL 2 Cl 2 ], only platinum­(IV) complexes were obtained .…”
Section: Synthesis Of Platinum(ii) Complexesmentioning
confidence: 99%